2014
DOI: 10.1002/jmri.24586
|View full text |Cite
|
Sign up to set email alerts
|

Prospective comparison of 3T MRI with diffusion‐weighted imaging and MDCT for the preoperative TNM staging of gastric cancer

Abstract: The diagnostic accuracy of 3T MRI is comparable to that of MDCT for the preoperative TNM staging of gastric cancer, and for assessing LN metastasis, the addition of DWI to conventional MRI may increase the sensitivity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
77
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 67 publications
(81 citation statements)
references
References 52 publications
(65 reference statements)
4
77
0
Order By: Relevance
“…Some studies have previously determined the ability of DW-MRI to detect, stage and assess tumor response in oncology (32,33,39,40). Liu et al .…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have previously determined the ability of DW-MRI to detect, stage and assess tumor response in oncology (32,33,39,40). Liu et al .…”
Section: Discussionmentioning
confidence: 99%
“…Some recent studies have demonstrated that DWI could perform well in the diagnosis and preoperative TNM staging of gastric cancer as well as that DWI could clearly show the border of gastric cancer and metastatic lymph nodes. Therefore, we could draw ROIs on DWI according to the staging criteria reported in previous published articles . More specifically, the signal intensity on DWI was low in normal and high in malignant muscle; as a result, we could exclude muscle in the case of T2 stage tumors.…”
Section: Methodsmentioning
confidence: 99%
“…Magnetic resonance imaging (MRI) has also been extensively employed in diagnosing gastric cancer. Diffusion‐weighted imaging (DWI), which reflects the Brownian movement of water molecules, can qualitatively and quantitatively provide morphologic and functional information about gastric cancers …”
mentioning
confidence: 99%
See 1 more Smart Citation
“…There was only one outlying study with a low specificity of MRI for T4 staging. 21 A sensitivity analysis was performed to investigate the influence of excluding the study on MRI specificity for T4 staging. We found that this analysis produced a higher estimate of specificity, and statistical heterogeneity of specificity in T4 stage tumour was diminished.…”
Section: Diagnostic Accuracy Of Primary Tumour Depth (T Stage)mentioning
confidence: 99%